Re: The engineer's instruction regarding incident at BRACU new campus project site - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the engineer's instruction regarding incident at BRACU new campus project site.